Complex revitalization of historically formed industrial territories in Kyiv in post-war recovery - Leshchenko, Nellya; Gulei, Daryna (Journal of Architecture and Urbanism, 2024)
The article is aimed at considering revitalization as a complex renewing method and a component of the complex process of restorative-reconstructive transformations of the historical urban environment. The effectiveness of complex revitalization with the involvement of various restoring and renewing methods has been proven. It allows at different system levels to revive and improve the quality of heterogeneous in terms of historical and architectural value and destruction of the historical urban environment, which usually includes the historically formed industrial territories. Such heterogeneity of the historical urban environment, reinforced over the last year by the devastating consequences of the war, today is characteristic of Kyiv and many cities of Ukraine, and therefore the proposed methodology is extremely relevant. The analysis of the experience of revitalizing former industrial territories of Lodz, as the most successful among the cities of Poland – the country with the closest historical, cultural, and architectural ties to Ukraine, is extremely valuable for pre-project studies of neglected and ruined historically formed industrial territories of Kyiv. The proposed concept of revitalizing degraded former industrial territories in Podil and on Radyshcheva Street in Kyiv has demonstrated the effectiveness of the proposed methodology.